Pengaruh Motivasi dan Kepuasan Kerja Terhadap Komitmen Organisasi Dengan Keterikatan Karyawan Sebagai Variabel Intervening - Rahmawati, Imel; Harini, Sri; Palahudin, Palahudin (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to determine the direct and indirect influence of motivation, job satisfaction on organizational commitment and employee engagement as an intervening variable at the New Ayuda Puncak Hotel. This research is quantitative research, using primary and secondary data where data collection uses field studies and literature studies. In this research the author used multiple linear regression analysis with the help of SPSS 25 and path analysis with the Sobel test. The sample in this research was all 63 hotel employees. The results of the research show that motivation and job satisfaction have a direct positive and significant effect on employee engagement, motivation and job satisfaction have a direct positive and significant effect on organizational commitment, organizational commitment has a direct positive and significant effect on employee engagement and employee engagement is able to mediate motivation and job satisfaction to organizational commitment.